Thermal decomposition behaviors, kinetics and thermodynamics of colemanite - POLAT, SEVGİ (My University, 2024)
Colemanite, the most significant commercially available borate mineral with calcium content, exhibits versatile applications and is widely used in glass, textiles, ceramics, detergents, and other industries. Investigating the dehydration characteristics, kinetics, and thermodynamics of this borate mineral is important to improve its performance because of its usage in different industries. This study involves a combination of characterization and thermal dehydration kinetics of colemanite results. First, colemanite is analyzed structurally and morphologically through X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), and scanning electron microscopy (SEM). Then, different heating rates were applied to investigate the thermal behavior of the colemanite using thermogravimetric analysis (TGA). Based on the obtained thermograms, the dehydration zone was selected for kinetic and thermodynamic analysis using conversional kinetic methods. The average activation energies were calculated as 64.1±4.3, 59.6±3.9, 59.9±3.7, and 60.0±4.1 kJ/mol for Flynn-Wall-Ozawa, Kissinger-Akahira-Sunose, Starink, and Tang models, respectively. Through the thermodynamic analysis, it was found that the dehydration of colemanite was a non-spontaneous and endothermic process.
Keywords: Colemanite; Morphology; Thermal kinetics; Thermodynamics